Neogene 3‐D Structural Architecture of The North‐West Apennines: The Role of the Low‐Angle Normal Faults and Basement Thrusts. Issue 7 (24th July 2018) - Molli, G.; Carlini, M.; Vescovi, P.; Artoni, A.; Balsamo, F.; Camurri, F.; Clemenzi, L.; Storti, F.; Torelli, L.
Abstract: The northern Apennines of Italy are a classical site for studying fundamental issues in tectonic studies, such as ophiolite formation and emplacement, kinematics of thrust wedges, role of in‐sequence and out‐of‐sequence thrusting, and of along strike segmentation, synorogenic versus postorogenic extension, and interplay between tectonics, erosion, and sedimentation. Accordingly, the northern Apennines have been extensively studied since more than two centuries ago. Despite the huge amount of available data with different resolution, a 3‐D comprehensive regional view combining in a modern framework all available surface and subsurface information for contiguous sectors of the chain is still lacking. We performed such an attempt in the area framed between the Taro valley to the north and the northern termination of the Alpi Apuane to the south. The region includes the main morphostructural zones of the north‐west Apennines from the Tyrrhenian coast (SSW of La Spezia), through the main topographic divide of the Apennines, up to the foothills range of the chain to the north. The area has been investigated through a multidisciplinary approach that integrated surface geological data, collected during the last two decades of structural and stratigraphic field works, and subsurface geological data. The construction of two regional NE‐SW trending cross sections (the Levanto‐Pontremoli‐Parma to the north and the La Spezia‐ Sarzana‐North Apuane‐Cerreto to the south), intersected by a NW‐SE trending Taro‐Lunigiana‐Alpi Apuane composite section, allowed us to illustrate (i) the role of out‐of‐sequence blind thrusting in the basement and (ii) the presence of low‐angle normal faulting and its relationships with recent to active high‐angle normal faulting. Both extensional and contractional systems have relevant implications for the tectonics of the northern Apennines as well as the seismotectonics of the studied region. Key Points: We present 3‐D frame for surface and subsurface structures of the North‐West Apennines We supply a more precise definition of the deep Apenninic tectonic structures focusing on the role of basement units and their characterization We emphasize the role of blind basement thrusts, the architecture of LANF systems, and overprint relationships with recent‐to‐active HANFs